CHALLENGES AND PROSPECTS IN THE SCIENTIFIC RESEARCH OF YOUNG SCHOLARS AND DOCTORAL STUDENTS (Universal International Scientific Journal, 2026)
This thesis examines the significant challenges faced by young scholars and doctoralstudents during the research process. It analyzes the underlying factors contributing to these challengesand identifies potential strategies for effective resolution. Particular attention is given to the vital role ofyoung researchers in advancing modern science, fostering innovative thinking, and enhancing researchcapacity within the context of globalization and the knowledge-based economy.
Keywords: young scientists; doctoral students; scientific research